1988
DOI: 10.1007/bf00045615
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the vertical structure of the tropical lowland rain forest of Los Tuxtlas, Mexico

Abstract: The vertical structure of one hectare of tropical rain forest was studied at Los Tuxtlas, State of Veracruz, Mexico. The structure was analysed at various scales of analysis, using different methodologies e.g. profile diagrams (0.1 ha) and vertical structure diagrams (1 ha). All profile diagrams suggested presence of stratification to some extent. However, simultaneous evaluation of several adjacent profile diagrams showed that the use of one profile diagram only can be very misleading: gaps or layers apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
8

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 13 publications
2
31
2
8
Order By: Relevance
“…According to Grubb et al (1963), the ratio of 'density at DBH class >10 cm' to 'density at DBH class >20 cm' can be used as a measure of the distribution of the different size classes. The patterns of species population structure detected were interpreted as a sign for the alteration in population dynamics in the forests (Popma et al, 1988).…”
Section: Data Analysesmentioning
confidence: 99%
“…According to Grubb et al (1963), the ratio of 'density at DBH class >10 cm' to 'density at DBH class >20 cm' can be used as a measure of the distribution of the different size classes. The patterns of species population structure detected were interpreted as a sign for the alteration in population dynamics in the forests (Popma et al, 1988).…”
Section: Data Analysesmentioning
confidence: 99%
“…Considering the extremes of the shade tolerance gradient as defined by RGRw in FU, these species are classified in accordance with other studies as shade intolerant or shade tolerant, and consequently found in gaps only or in the forest understorey as well (Martinez-Ramos 1985). Several species with intermediate growth rates and similar growth responses to gaps however are sometimes more frequent in shaded habitats (Psychotria, Cordia) or in late secondary vegetation (Omphalea, Lonchocarpus) (Bongers et al 1988 a;Martlnez-Ramos 1985;Purata-Velarde 1986). This suggests that these species may be differentiated in other aspects than their growth response in the seedling stage, notably seed dispersal, competitive ability, herbivore defense, pathogen resistance (Augspurger 1984 a;Clark and Clark 1985), and acclimation potential (Fetcher et al 1983;Oberbauer and Strain 1985).…”
Section: Species Differentiationmentioning
confidence: 99%
“…(1968), en las selvas dominadas por Terminalia amazonia de la planicie costera del Golfo de México y Meave del Castillo (1983) en la selva Lacandona, Chiapas, reconocieron tres y cuatro estratos arbóreos, respectivamente, en función de la altura media y máxima de los individuos de sus especies; ambos autores señalan que dichos estratos pudieron ser artificiales, pero los consideraron necesarios para reconocer en función del índice de dominancia, los cambios en la estratificación vertical. Posiblemente esta complejidad de la selva alta condujo a Popma et al (1988) a distinguir sólo el sotobosque y una selva no estratificada en su estudio en la región de los Tuxtlas, Veracruz. En el presente trabajo, se pudo reconocer en el campo, gracias al profundo conocimiento de los lacandones, la existencia de seis estratos bien definidos: uno herbá-ceo, otro arbustivo y cuatro arbóreos con composición florística y formas vitales predominantes distintivas para cada uno.…”
Section: Discussionunclassified